Aplikasi Elaboration Likelihood Model Theory dalam Iklan Calon Gubernur 2018 terhadap Perilaku Memilih - Fitri Norhabiba (Kanal: Jurnal Ilmu Komunikasi, 2018)
The election of the head of the region would be held by government. It brought its own benefits to the campaign team. It was easy to find even before the pairing, the candidates who would forward to show his face in a billboard or banner on the sidewalk. Their poses for religious festivities or bright invokes blessings. They described in doing many positive activities to attract people's sympathy. Many governor candidates used outdoor media to advertise them in the governor election last June. Generally they showed self-advertising positively, memorable, and interesting. There were characteristics that highlighted. So, prospective voters would remember and did not hesitate to vote. This was the usual way of using elaboration likelihood theory either on peripheral routes or central routes. The central route involved critical thinking that peripheral routes did not do that. This theory was also associated with the behavior of people’s vote. The results of this conceptual study showed the finding that visible things are visually capable of capturing unselected voters with peripheral routes. In the other hand, voters who used the central route were given a lot of informative information to reinforce belief.